Nuclear transfer nTreg model reveals fate-determining TCR-β and novel peripheral nTreg precursors - Ku, Manching (Proc Natl Acad Sci U S A, 2016)
To study the development and function of “natural-arising” T regulatory (nTreg) cells, we developed a novel nTreg model on pure nonobese diabetic background using epigenetic reprogramming via somatic cell nuclear transfer. On RAG1-deficient background, we found that monoclonal FoxP3(+) CD4(+) Treg cells developed in the thymus in the absence of other T cells. Adoptive transfer experiments revealed that the thymic niche is not a limiting factor in nTreg development. In addition, we showed that the T-cell receptor (TCR) β-chain of our nTreg model was not only sufficient to bias T-cell development toward the CD4 lineage, but we also demonstrated that this TCR β-chain was able to provide stronger TCR signals. This TCR-β–driven mechanism would thus unify former per se contradicting hypotheses of TCR-dependent and -independent nTreg development. Strikingly, peripheral FoxP3(−) CD4(+) T cells expressing the same TCR as this somatic cell nuclear transfer nTreg model had a reduced capability to differentiate into Th1 cells but were poised to differentiate better into induced nTreg cells, both in vitro and in vivo, representing a novel peripheral precursor subset of nTreg cells to which we refer to as pre-nTreg cells.